Identifikacija vročih točk geodiverzitete na primeru krajinskega parka Rakov Škocjan - Stepišnik, Uroš (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2015)
Regardless of numerous methods of geodiversity evaluation, subjective criteria based methods prevail what reflects in the quality and comparability of data. The purpose of this article is to present the application of geodiversity evaluation method, which is largely stripped of subjective factors. The method we used to calculate the geodiversity index is based solely on surface ruggedness and spatial distribution of geosites was applied in the area of Rakov Škocjan Landscape Park.
Keywords: environmental protection; geološka dediščina; geomorfologija; geomorphology; naravna dediščina; Rakov Škocjan; Rakov Škocjan, Cerknica; varstvo okolja